RETRACTED: Contribution of parental attention and learning motivation to career planning of vocational school students - Atikah Rahmah Nasution; A. Muri Yusuf (Universitas Negeri Padang, 2021)
RETRACTION TO:Nasution, A., & Yusuf, A. (2021). Contribution of parental attention and learning motivation to career planning of vocational school students. Konselor, 10(1). doi:https://doi.org/10.24036/02021101112102-0-00This article has been retracted by Publisher based on the following reason:The Editor of KONSELOR found the double publication in the article publishing due to article's content similarity published in http://bk.ppj.unp.ac.id/index.php/ijacss/article/view/421Nasution, A. R., & Yusuf, A. M. (2021). Parental Attention and Learning Motivation Contribution to Career Planning of Vocational School Students. International Journal of Applied Counseling and Social Sciences, 2(2), 126-133.One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process